Philosophy and the human sciences : philosophical papers 2 - Taylor, Charles 1931- (Cambridge University Press, 1985)
Taylor taught political science and philosophy for many years at McGill. He is also one of CanadaÕs best know public intellectuals, as evident in his delivery of the 1991 Massey Lectures, co-authorship of the 2008 Bouchard-Taylor report on reasonable accommodation in Quebec, and winner of the U.S.$1.5 million Templeton Prize, the largest philanthropic award that a single person can win. IÕve written before about my disagreement with TaylorÕs theory of multiculturalism, but he has written on a wide variety of topics, often with great insight. Taylor is an especially eloquent proponent of the idea that social science is something of a misnomer: the study of human beings inevitably requires interpretation and judgement, and so cannot be modeled after the natural sciences and the kind of objectivity they aspire to. When I first read Taylor as an undergraduate at a liberal arts college I thought this point was so obvious it hardly required stating. After enrolling in a PhD program at a large research university however I came to see that it is actually somewhat iconoclastic, as there have beenÑand still areÑmany academic movements that have sought to establish a science of human affairs, whether in psychology, economics or political science (even the name of the latter discipline is an example of the mindset Taylor is criticizing). Philosophical Papers Volume II contains TaylorÕs brilliant essay on this theme, ÒInterpretation and the Sciences of Man.Ó It also has another excellent essay, ÒWhatÕs Wrong with Negative Liberty,Ó one of the most insightful critiques of libertarianism IÕve ever read. Interestingly, scientism and libertarianism are both intellectual movements that have thrived more in the USA than Canada, and TaylorÕs salutary influence may be one reason why.